Rainfall-induced landslides in Himachal Pradesh: a review of current knowledge and research trends - Prince Tailey Jallayu; Kanwarpreet Singh; Kennedy C. Onyelowe; Abhishek Sharma; Aditya Kumar Tiwary (Cogent Engineering)
This review synthesizes the existing literature on rainfall-induced landslides in Himachal Pradesh, India. A thorough literature search was conducted to locate pertinent studies published from 2014 to 2024 to capture recent advancements in this field. This timeframe allows for a focused analysis of contemporary research while maintaining a manageable scope for this review. The analysis of 74 peer-reviewed articles and conference papers revealed that landslides in Himachal Pradesh are significantly influenced by steep slopes, weak geological formations, intense rainfall, and anthropogenic activities. Shimla, Mandi, Solan, and Sirmaur districts exhibited the highest landslide frequencies. Key research gaps identified include the impact of climate change on rainfall patterns and landslide occurrence, the need for real-time rainfall data integration into early warning systems, and the development of affordable and sustainable mitigation measures. This review highlights the urgent need for improved landslide risk management strategies in Himachal Pradesh, emphasizing the potential for significant reductions in loss of life and property through pinpointing high-risk zones and establishing effective early warning systems. The findings provide a valuable resource for researchers, policymakers, and practitioners involved in mitigating landslide risks in the region. This review provides a comprehensive overview of the current knowledge on rainfall-induced landslides in Himachal Pradesh, highlighting the research gaps and areas for future investigation. This, in turn, informs the development of effective landslide risk management strategies, serving as a valuable resource for researchers, policymakers, and practitioners dedicated to mitigating landslide risks.